Sustainability in Open Distance Learning (ODL): Adoption of Market Segmentation and Advertising Strategy - Mohd Nazri Mohd Noor; Azlina Abdul Aziz; Yanty Roslinda Harun; Norsiah Aminudin; Zulaikha Zakariah; Ignasius Heri Satrya Wangsa (2022)
The purpose of this paper is to examine the prospective learner’s perception of effective market segmentation and advertising messages for open distance learning (ODL) advertisements. A descriptive study was conducted to assess the perceptions of prospective ODL learners in Malaysia. Selfadministered questionnaires were used to obtain meaningful data from 314 respondents. The study was conducted from January to March, 2021. Based on the analysis, accessibility between the ODL institution and its market segments was viewed by the majority of the respondents as more important than substantiality. Furthermore, the respondents agreed that reminders and persuasive messages are significant in attracting audience attention to an ODL institution. The standardised path coefficients have shown that accessibility, reminders and persuasive messages are significant predictors of the sustainability of ODL institutions, whereas substantiality was perceived by the respondents as being insignificant. The results from this study will help ODL institutions be more focused when designing their advertising messages, and will deepen their understanding of market needs. These findings have strong implications for academic ODL institutions, particularly in the aspect of institutional sustainability based on effective market segmentation and the right strategy of advertising messages.